DAMPAK KEIKUTSERTAAN ASURANSI KETENAGAKERJAAN DALAM MENINGKATKAN KINERJA DI KANTOR BPJS KETENAGAKERJAAN CABANG MAKASSAR - Muhammad Irwan Nur Hamiddin (Journal Of Business, Finance, and Economics (JBFE), 2022)
Globalization has caused Indonesia to be flooded with world-class insurance companies that provide excellent service for workers in Indonesia. What is the main challenge is how the readiness of national insurance companies or the government is given the responsibility of providing services for workers who cannot borne by insurance companies that are only profit-oriented.